Physical mixture of a cyclic lipopeptide vaccine induced high titres of opsonic IgG antibodies against group A streptococcus. (1st December 2021) - Madge, Harrison Y. R.; Huang, Wenbin; Gilmartin, Lachlan; Rigau-Planella, Berta; Hussein, Waleed M.; Khalil, Zeinab G.; Koirala, Prashamsa; Santiago, Viviene S.; Capon, Robert J.; Toth, Istvan; Stephenson, Rachel J.
Abstract : The presence of a cyclic peptide is as part of a physically-mixed group A Streptococcus vaccine for the induction of a strong, balanced Th1/Th2 immune response. Abstract : Untreated or reoccurring group A Streptococcus (GAS) infection can lead to a number of post-infection complications, including rheumatic heart disease. There is no licenced vaccine for the treatment or prevention of GAS infection. We identified that a cyclic decapeptide plays a significant positive influence on the adjuvant activity of several lipid-antigen mixtures. Here, three synthetic vaccine components were synthesised: (1) J8-PADRE represents the GAS B cell antigen (J8) conjugated to the universal T helper epitope (PADRE); (2) a synthetic toll like receptor 2 (TLR2) ligand based on a C16 alkyl chain lipid moiety; and (3) a cyclic carrier deca-peptide. Previously, through structure-immune activity investigations, it was observed that a physical mixture of these three components had significantly higher IgG immune responses when compared to a fully conjugated vaccine construct. Expanding the scope of this structure–activity investigation, we show that the presence of the cyclic peptide is required for the induction of a strong, balanced Th1/Th2 immune response when compared with lipid and antigen only, and cyclic lipopeptide plus B/T cell antigen physical mixtures.